Plataformas educativas virtuales y su incidencia en el desempeño académico en el área de Ciencias Sociales de los estudiantes de la básica secundaria (2019)
Educational practice in the 21st century cannot be behind the scientific and technological advances, which is why the inclusion of ICTs in education will allow a better way of teaching and also how what learners learn; therefore, this research work aims to analyze the incidence of virtual educational platforms, in the academic performance in the area of social sciences of secundary School students. The research is worked under a quantitative, descriptive approach and a quasi-experimental design. For which, a sample of 80 6th grade students of the Dolores María Ucros Educational Institution in intentionally selected. During the development of the research, a diagnosis is made of the status of academic performance obtained during the first semester of de year 2019 in the area of social; then pedagogical strategies are applied for teaching and learning in the area using the EDMODO plataforma during the second academic semester and at the end, a test is appliedto assess the impact that the implementation of teaching strategies had with the use of technological platforms in the performance, and finally, the results of the test were compared with the academic performance obtained by the students in the first semester. The results obtained from the research show that 95% of the students indentify the use of technical and technological resources for leisure and communication in a precarious way and in most cases with inappropriate uses; during the School activities the most frequent resource they use is the internet for superfluous consultations since the handling of Word processors and other common tools constitute a tedium factor for the students performance; the first comparison shows us through the consolidated results that the students performance had a significant increase after the application of strategies and activities mediated by the tics. It is concluded thatthe low performance obtained by students, is largely due to the absence of innovative pedagogical activities. The use of technical and technological resources motivates students for the learning of social sciences, since students consider their boring and uninteresting teaching when it is done with traditional methodologies; since it presents to them very abstrac concepts and facts distant from their realities.